A Hydrosuction Siphon System to Remove Particles Using Fan Blades - Rasool M.H.; Zainol M.R.R.M.A.; Noor N.M.; Aziz M.S.A.; Zawawi M.H.; A. Wahab M.K.; Abu Bakar M.A. (MDPI, 2024)
Sedimentation in dam reservoirs can cause problems that lead to loss of storage capacity and decrease in the flood control volume. Hydrosuction sediment removal is one of the methods used to remove sediments from within a reservoir using the suction energy provided by the effective head. In this study, a new tool has been developed by attaching the reservoir to a suction pipe intake point and using a simple fan blade mechanism for the hydrosuction sediment removal system. This mechanism is used to create a vortex flow to suspend the settled particles. This paper investigated the effects of the fan blade angles, effective head, and inlet height from the surface of layer particles on the performance and efficiency of fan blades hydrosuction sediment removal (FBHSSR) and hydrosuction sediment removal (HSSR) systems based on the geometric scour hole parameters. Results from the experimental tests indicated the effectiveness of the FBHSSR system, with the fan blade angles of 30, 45, and 60 leading to approximately 800%, 200%, and 117%, respectively, removed particles greater than those of the HSSR system. Furthermore, the maximum depth and diameter of the scour hole were increased by 206%, 200%, and 137% and 135, 112%, and 117%, respectively, for each angle. The effective head or experiment time also enhanced system performance by increasing the suction discharge, but no change was observed in terms of efficiency. The critical inlet heights for the FBHSSR and HSSR systems are 1 time and 2.54 times, respectively, more than the diameter of the suction pipe. Thus, it can be concluded that using fan blades in HSSR systems is a good approach to improve the properties of the scour hole. 2023 by the authors.